Characterization and optimization of heavy metals biosorption by fish scales - Othman, Norzila (2011)
Heavy metals are highly toxic and cumulative poison. Once in the environment, it is difficult to recover and can adversely affect human health. The tremendous increse in the use of heavy metals over the past few decades has inevitably increased the metallic contents in the aquatic life. Heavy metals ions are of great concern, due to their mobility in natural water ecosystems and due to their toxicity.Removal of nickel from aqueous solution using tilapia fish scale as biosorbent was studied. This study was focused on the evalution of the impact of amount of biosorbent, pH and contact time on nickel ions removal from aqueous solution using tilapia fish scale as biosorbent. The optimum percentage removal value was found as 71.25% with the amount of 2g tilapia fish scale biosorbent. Optimum percentage uptake was found to occur at alkaline equilibrium reached after four hours contact time with 70% and 1.4 mg/g respectively.The finding indicated that promising biosorption of nickel using tilapia fish scale as biosorbent.